EsGPCR89 regulates cerebral antimicrobial peptides through hemocytes in Eriocheir sinensis. Issue 95 (December 2019) - Qin, Xiang; Jin, Xingkun; Zhou, Kaimin; Li, Hao; Wang, Qiying; Li, Weiwei; Wang, Qun
Abstract: G protein-coupled receptors (GPCRs) are important transmembrane receptors that participate in diverse physiological processes including metabolism, cell growth and immune processes by transmitting extracellular signals to intracellular effectors. In this study, a gene belonging to the GPCR family was cloned from Eriocheir sinensis and named Es GPCR89. The full-length gene includes an open reading frame (ORF) of 465 amino acid residues, and bioinformatic analysis confirmed the high conservation between species. Es GPCR89 was detected in various tissues of E. sinensis, and was up-regulated in brain following Staphylococcus aureus infection. Expression levels of cerebral antimicrobial peptides (AMPs) were also up-regulated following bacterial challenge, reflecting their function in cerebral immunity. Additionally, Es GPCR89 silencing in hemocytes by RNA interference, down-regulated AMPs in brain after S. aureus infection. Moreover, through Immunisation assay and Polyacrylamide gel electrophoresis (SDS-PAGE) experiments, we could infer that bacterially infected hemocytes released effectors under the regulation of EsGPCR89, thereby activating transcription of cerebral AMPs. These results demonstrate that Es GPCR89 plays important roles in cerebral antimicrobial function via hemocytes. Highlights: Cerebral AMPs are also up-regulated following bacterial challenge. Es GPCR89 silencing in hemocytes down-regulates brain AMPs after S. aureus infection. Es GPCR89 mediates cerebral antimicrobial function via hemocytes.